2021
DOI: 10.1111/trf.16454
|View full text |Cite
|
Sign up to set email alerts
|

Joint Trauma System, Defense Committee on Trauma, and Armed Services Blood Program consensus statement on whole blood

Abstract: Hemorrhage is the most common mechanism of death in battlefield casualties with potentially survivable injuries. There is evidence that early blood product transfusion saves lives among combat casualties. When compared to component therapy, fresh whole blood transfusion improves outcomes in military settings. Cold‐stored whole blood also improves outcomes in trauma patients. Whole blood has the advantage of providing red cells, plasma, and platelets together in a single unit, which simplifies and speeds the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 17 publications
0
32
0
4
Order By: Relevance
“…Finally, the use of whole blood resuscitation, specifically cold-stored low-titer group O whole blood, is having a resurgence in trauma care. The Joint Trauma System has put forth guidelines on whole blood transfusion in military settings, where whole blood transfusion has been shown to improve outcomes [122] , and there is growing evidence to support the use of whole blood in civilian trauma [123] . Importantly, whole blood can be administered more easily and rapidly than individual component therapy.…”
Section: Plasma Protection Of the Endothelial Glycocalyx And Vascular...mentioning
confidence: 99%
“…Finally, the use of whole blood resuscitation, specifically cold-stored low-titer group O whole blood, is having a resurgence in trauma care. The Joint Trauma System has put forth guidelines on whole blood transfusion in military settings, where whole blood transfusion has been shown to improve outcomes [122] , and there is growing evidence to support the use of whole blood in civilian trauma [123] . Importantly, whole blood can be administered more easily and rapidly than individual component therapy.…”
Section: Plasma Protection Of the Endothelial Glycocalyx And Vascular...mentioning
confidence: 99%
“…Although this practice change predominantly occurred in the civilian domain, whole blood continued to be a mainstay of resuscitation during the Iraq and Afghanistan wars [5]. Whole blood use was associated with a reduction in mortality and a decrease in blood product usage, and the Department of Defense Joint Trauma System and the Committee on Tactical Combat Casualty Care subsequently developed guidelines encouraging the use of whole blood in the prehospital setting [6,7]. A recent survey of 103 level one trauma centers reported that 42% of respondents utilize whole blood in the resuscitation of trauma patients, with all but 12% of those centers placing restrictions on number of units transfused [8].…”
Section: History Of Whole Blood Utilizationmentioning
confidence: 99%
“…Successful experience with fresh whole blood by the US military is well documented [ 125 ]. Recent studies suggest that LTOWB in resuscitation of civilian trauma is associated with a reduction in post-emergency department transfusions and increase likelihood of 24-h and 28-day survival [ 120 , 126 ].…”
Section: Management Of the Polytrauma Victimmentioning
confidence: 99%